Trends in US minority red blood cell unit donations. Issue 5 (16th February 2017) - Yazer, Mark H.; Delaney, Meghan; Germain, Marc; Karafin, Matthew S.; Sayers, Merlyn; Vassallo, Ralph; Ziman, Alyssa; Shaz, Beth; ,
Abstract : BACKGROUND: To provide the appropriately diverse blood supply necessary to support alloimmunized and chronically transfused patients, minority donation recruitment programs have been implemented. This study investigated temporal changes in minority red blood cell (RBC) donation patterns in the United States. STUDY DESIGN AND METHODS: Data on donor race and ethnicity from 2006 through 2015, including the number of unique donors, collections, RBCs successfully donated, and average annual number of RBC donations per donor (donor fraction), were collected from eight US blood collectors. Minority donors were stratified into the following groups: Asian, black or African American, Hispanic or Latino, Native Indian or Alaska Native, Native Hawaiian or other Pacific Islander, white, multiracial/other, and no answer/not sure. RESULTS: Over the 10‐year period, white donors annually constituted the majority of unique donors (range, 70.7%‐73.9%), had the greatest proportion of collections (range, 76.1%‐79.8%), and donated the greatest proportion of RBC units (range, 76.3%‐80.2%). These donors also had the highest annual donor fraction (range, 1.82‐1.91 units per donor). Black or African American donors annually constituted between 4.9 and 5.2% of all donors during the study period and donated between 4.0 and 4.3% of all RBC units. Linear regression analysis revealed decreasing numbers of donors, collections, and donated RBC units from white donors over time. CONCLUSION: Although the US population has diversified, and minority recruitment programs have been implemented, white donors constitute the majority of RBC donors and donations. Focused and effective efforts are needed to increase the proportion of minority donors.